'I do not cognize myself through being conscious of myself as thinking': Self-knowledge and the irreducibility of self-objectification in Kant. Issue 7 (3rd October 2019) - Khurana, Thomas
ABSTRACT: The paper argues that Kant's distinction between pure and empirical apperception cannot be interpreted as distinguishing two self-standing types of self-knowledge. For Kant, empirical and pure apperception need to co-operate to yield substantive self-knowledge. What makes Kant's account interesting is his acknowledgment that there is a deep tension between the way I become conscious of myself as subject through pure apperception and the way I am given to myself as an object of inner sense. This tension remains problematic in the realm of theoretical cognition but can be put to work and made productive in terms of practical self-knowledge.